Answer:
<em>Step 1: 4 x − 3 − 2 x − 10 </em>
<em>Step 2: 2 x − 13</em>
Step-by-step explanation:
Given the expression;
(4 x − 3) − 2 (x + 5)
The following steps/ procedure are to be taken when simplifying the expression.
open the parenthesis
(4 x − 3) − 2 (x + 5)
= 4x-3 -2(x)-2(5)
= 4x-3-2x-10
collect the like terms
= 4x-2x-3-10
simplify the resulting expression
= 2x-13
Hence the procedure that correctly simplifies the expression are:
Step 1: 4 x − 3 − 2 x − 10
Step 2: 2 x − 13
If is an acute triangle, all the angles should be acute angles.
180-38=142°
142-69=73°
So your answer is 69°, lovely~
Answer:
y=a-4 divided 3-a and a cut so remember 4divided3 so, y= 1.33
Step-by-step explanation:
Answer:
1/14
Step-by-step explanation:
1/2+3/7=7/14-6/14=1/14
*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆**☆*――*☆*――*☆*――*☆
Answer: 382.5
Explanation:
450 x .85 = 382.5
I hope this helped!
<!> Brainliest is appreciated! <!>
- Zack Slocum
*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆**☆*――*☆*――*☆*――*☆